(untitled) (Medical Forum Monthly, 2024)
Objective: To assess the association between diabetes mellitus and chronic renal failure with toxic effects of chromium on the onset of the Chronic Kidney disease. Study Design: A prospective cross sectional study. Place and Duration of Study: This study was carried out at the Jinnah Post graduate Medical Centre and Kidney Centre Karachi during December 2012 to December 2013. Materials and Methods: The present study was conducted on a total of 150 patients (age > 40 years) divided into three groups. Patients in Group I included 50 patients with diabetes mellitus type 2 whereas Group II included 50 patients with diabetes mellitus associated with chronic renal failure (CRF) and Group III consisted of 50 healthy controls. Results: Results showed that levels of fasting blood sugar and HbA1c in both group I and group II were significantly high where as it was lower in controls. Serum urea (125.2 ± 32.49) and creatinine (7.3 ± 1.41) levels in patients with DM with CRF were significantly high as compared to patients with DM only and control group. The Creatinine clearance (55.1 ± 9.61) in patients with DM with CRF was decreased in comparison with DM patients and control group. Serum chromium levels were significantly high in patients with DM with CRF and in patients with DM. Conclusion: Serum chromium level showed significant correlation with glycemic index when the two groups including DM patients and patients with DM accompanied with CRF were compared with the controls, while correlation with renal failure was significant only in group II patients.